1982
DOI: 10.1038/hdy.1982.63
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for preferential mating in Adalia bipunctata

Abstract: SUMMARYNon-random mating may be involved in the maintenance of colour polymorphism in Adalia bipunctata. Mating choice experiments have been carried out on a stock of A. bipunctata from Keele. Specific frequencies of the melanic quadrimaculata form and the non-melanic typica form were placed in population cages or mating chambers and allowed to mate. The frequencies of the forms amongst mating pairs were scored. The results gave a good fit to a model of mixed sexual selection and assortative mating showing a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 8 publications
(7 reference statements)
5
50
0
Order By: Relevance
“…Keele was the first British population in which sexual selection for melanics was demonstrated (Majerus et al, 1982a). Samples from the Keele population were then used for our first experiments to select for preference (Majerus et al, 1 982b) and to set up MOKFs original isofemale lines.…”
Section: One Of Majerus' Contributors To the Cambridgementioning
confidence: 99%
“…Keele was the first British population in which sexual selection for melanics was demonstrated (Majerus et al, 1982a). Samples from the Keele population were then used for our first experiments to select for preference (Majerus et al, 1 982b) and to set up MOKFs original isofemale lines.…”
Section: One Of Majerus' Contributors To the Cambridgementioning
confidence: 99%
“…This was a selection experiment. Majerus, O'Donald and Weir (1982a) showed that both in natural populations in the field and in experimental populations in the laboratory, the melanic quadrimaculata males of the Two-spot Ladybird, Adalia bipunctata have a mating advantage that fits a simple model of preferential mating. If this is produced by a genetically determined female preference, it should be possible to select for increased preferential mating in the population.…”
Section: Introductionmentioning
confidence: 99%
“…Mader, 1926-37;Lus, 1928;1932). Often, they are grouped together for convenience as the form annulata (Creed, 1966;Majerus et a!., 1982a). Lus (1928Lus ( , 1932 was the first to work on the genetics of this polymorphism, which he explained in terms of multiple alleles at a single locus.…”
Section: Introductionmentioning
confidence: 99%